Safety of Allanblackia seed oil for extended uses in vegetable oils and milk and in yellow fat and cream‐based spreads up to 30% (w/w) - Turck, Dominique (EFSA J, 2018)
In 2007, the EFSA NDA Panel concluded that Allanblackia seed oil obtained from the seeds of Allanblackia trees is safe for human consumption under the proposed conditions of use. Due to its high contents of stearic‐oleic‐stearic and stearic‐oleic‐oleic triglycerides, which made the oil suitable as a ‘hardstock’ component, the applicant applied for its use as a novel food (NF) ingredient in yellow fat and cream‐based spreads at a level of 20% (w/w). In this application, the applicant seeks (1) to increase the authorised maximum use level (i.e. 20% w/w) in yellow fat spreads and cream‐based spreads to 30% (w/w) and (2) the use of this NF in mixes of vegetable oils and milk up to a maximum use level of 30% (w/w). (3) The applicant proposes also some changes in the specifications of the NF, although he noted that the oil is collected, extracted and refined using the same processes that are currently used for other edible vegetable oils and which have been evaluated in the original application assed by EFSA in 2007. According to the information provided by the applicant, the production process and the composition of the NF do not change. The Panel notes that the revised specification limits on trans‐fatty acid (TFA), unsaponifiable matter, peroxide value are similar to those for other edible oils and fats. The applicant also indicated that he had performed an updated comprehensive literature search using several different databases, but no preclinical studies or human studies on Allanblackia seed oil were identified which have not been provided for the previous EFSA assessment in 2007. The Panel notes that the proposed extended uses would increase the potential intake of the NF, which is considered not to be nutritionally disadvantageous. The Panel concludes that Allanblackia seed oil is safe at the extended uses and use level.